Die Toten (Les morts, 1998) de Hans-Peter Feldmann, ou la réconciliation visuelle entre mémoire et événement - Daniela Kneissl (Images Re-Vues)
Published in 1998, the book Die Toten (The Dead) by the German artist Hans-Peter Feldmann brings together the photographs of people killed in the violent actions perpetrated by the left-wing terrorists – the RAF above all – who perturbed the Federal Republic in the 1970s and 1980s. The book consists exclusively of photographic reproductions taken from the press, the first communication medium to inspire Feldmann’s work. Conceived as a chronological gallery of the facts the book has been criticised for mixing the images of terrorists killed with those of their intended or accidental victims. According to the critics erasing the media context and the historical narrative has contributed to creating a myth about leftist terrorism. The article supports the thesis that Feldmann’s artistic strategy, far from glorifying or minimising brutal historical reality, ought rather to be considered as an element in a wider culture of memory and mourning, recalling the human side of this black chapter in recent German history in all its fullness. By reconstituting terrorism in images as a continuous event Feldmann has taken the inventory of a collective menace.